2013
DOI: 10.4318/tjg.2013.0610
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and endoscopic predictors of colorectal adenoma recurrence after colon polypectomy

Abstract: Girifl ve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
3
4
1
Order By: Relevance
“…Patients without a baseline adenoma have a quantifiable risk of AA within 1−5 years. In accordance with other studies, we found that patients with an increased number (≥3 NAA) and with both proximal and distal NAAs at baseline had an increased risk of subsequent adenomas. As in other studies we found that age ≥50 years, male gender and a family history of CRC were also associated with colon neoplasia during follow‐up and that over 50 years old and male gender were independent factors for AA .…”
Section: Discussionsupporting
confidence: 92%
“…Patients without a baseline adenoma have a quantifiable risk of AA within 1−5 years. In accordance with other studies, we found that patients with an increased number (≥3 NAA) and with both proximal and distal NAAs at baseline had an increased risk of subsequent adenomas. As in other studies we found that age ≥50 years, male gender and a family history of CRC were also associated with colon neoplasia during follow‐up and that over 50 years old and male gender were independent factors for AA .…”
Section: Discussionsupporting
confidence: 92%
“…Variable rates of RRA continue to challenge the effectiveness of colorectal EMR. Several studies have been conducted to find potential clinical and endoscopic predictors for recurrence 2 3 7 8 9 10 19 20 . A recent metanalysis of 30 articles and 3404 patients undergoing EMR reported an overall rate of recurrence of 13.1 % 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Intralesional and extralesional risk factors for adenoma recurrence after EMR have been well described in multiple studies 2 7 8 9 10 11 . A more recent prospective multicenter study by Tate et al 12 proposed a scoring model for stratification of recurrence risk after EMR.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies reported that older age and male sex were associated with a higher risk of adenoma recurrence. [ 9 12 23 24 ] However, data regarding the influence of modifiable risk factors, such as metabolic factors, on adenoma recurrence are extremely limited. Thus, we conducted this longitudinal study to identify patient-related risk factors associated with the occurrence of colorectal adenomas at time of follow-up surveillance colonoscopy, especially focusing on metabolic factors.…”
Section: Introductionmentioning
confidence: 99%